The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1104/pp.105.074690
|View full text |Cite
|
Sign up to set email alerts
|

Adducts of Oxylipin Electrophiles to Glutathione Reflect a 13 Specificity of the Downstream Lipoxygenase Pathway in the Tobacco Hypersensitive Response

Abstract: The response to reactive electrophile species (RES) is now considered as part of the plant response to pathogen and insect attacks. Thanks to a previously established high-performance liquid chromatography tandem mass spectrometry methodology, we have investigated the production of oxylipin RES adducts to glutathione (GSH) during the hypersensitive response (HR) of plants. We have observed that RES conjugation to GSH in tobacco (Nicotiana tabacum) leaves is facile and nonspecific. In cryptogein-elicited tobacc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 52 publications
3
80
0
1
Order By: Relevance
“…3). Such GSH conjugates accumulate in plants fed with oxylipins or exposed to infection (30,31). Although it is possible that GSTUs bind these conjugates after their spontaneous glutathionylation, our studies demonstrated that GSTU19 and other GSTUs actively catalyzed the formation of the OPDA conjugate.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…3). Such GSH conjugates accumulate in plants fed with oxylipins or exposed to infection (30,31). Although it is possible that GSTUs bind these conjugates after their spontaneous glutathionylation, our studies demonstrated that GSTU19 and other GSTUs actively catalyzed the formation of the OPDA conjugate.…”
Section: Discussionmentioning
confidence: 82%
“…The physiological consequence of oxylipin conjugation in plants is unknown, although similar derivatives of the chemically related leukotrienes are known to be bioactive in mammals (32). It is also of interest that OPDA is an intermediate in jasmonic acid synthesis and that GSTU19 may have a role in regulating the passage of this compound from the chloroplast to the peroxisome (31).…”
Section: Discussionmentioning
confidence: 99%
“…This acetylation has been hypothesized to play a role in the inactivation and turnover of C6-aldehydes (d 'Auria et al, 2006;Farag et al, 2005). Secondly, in addition to acetylation, exogenously applied E-2-hexenal can also undergo conjugation to glutathione (GSH), leading to the formation of E-2-hexenal GSH adducts in the form of 1-hexanol-3-GSH (Davoine et al, 2006). Conjugation to GSH is a well-known mechanism to inactivate reactive molecules (Coleman et al, 1997).…”
Section: Gaba Stimulates Root Growth Of E-2-hexenal-treated Her1 Seedmentioning
confidence: 99%
“…The solution was centrifuged at 8000 g for 5 min and, subsequently, the supernatant was filtered and used for the electrospray ionization HPLC-MS 2 analysis according to the method described by Davoine et al (2005). Quantification was carried out in the MRM mode, following the specific mass transition 408 fi 279 corresponding to the loss of glutamyl (129) from the ion (1-hexanol -3-GSH + H + ) as described by Davoine et al (2006).…”
Section: Determination Of Gsh Adduct Levelsmentioning
confidence: 99%
See 1 more Smart Citation